The Girls : A Novel - Lansens, Lori (London Virago, 2011)
The girls, Rose and Ruby Darlen, were born joined at the head in a rural farming community in 1974. Abandoned by their frightened teenage mother, they are adopted by the eccentric nurse who attended their birth, and her husband, a gentle immigrant butcher